Qualitative feed restriction for heavy swines: effect on digestibility and weight of organs of digestive tract, and environmental impact of feces - Fraga, A.L.; Thomaz, Maria Cristina [UNESP]; Kronka, R.N. [UNESP]; Budiño, F.E.L. [UNESP]; Huaynate, R.A.R. [UNESP]; Scandolera, A.J.; Ruiz, U.S. [UNESP]; Nadai, A. (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2009)
Foram utilizados 50 suínos machos castrados para avaliar o efeito da restrição alimentar qualitativa sobre a digestibilidade dos componentes dietéticos, os órgãos do trato digestório, a composição e a produção fecal. Foram utilizadas cinco dietas experimentais, com níveis de restrição qualitativa de 0, 5, 10, 15 e 20%. Houve redução linear (P<0,001) para todos os coeficientes de digestibilidade, com exceção da fibra em detergente ácido, que apresentou resposta quadrática (P<0,05). Os teores de sólidos totais (P<0,01) e voláteis (P<0,05), e minerais totais (P<0,001) nas fezes aumentaram com os níveis de restrição alimentar, enquanto os níveis de K (P<0,05), Cu (P<0,01) e de N, P, Na, Ca, Mg, Fe e Zn (P<0,001), apresentaram resposta quadrática. A excreção diária de fezes, sólidos totais e voláteis, minerais totais, N, P, K, Mn e Cu (P<0,001), Ca, Na, Mg e Fe (P<0,05) apresentaram aumento em função do nível da restrição alimentar qualitativa. A restrição qualitativa pode ser alternativa para destinação de resíduos da agroindústria, conferindo boas propriedades às fezes suínas, no que diz respeito à utilização para adubação de culturas.

A total of 50 barrows were used to evaluate qualitative feed restriction on digestibility of dietary components, weight of organs of digestive tract, and composition and production of feces. Five experimental diets, with increasing levels of qualitative feed restriction of 0, 5, 10, 15, and 20% were used. There was linear reduction (P<0.001) of all digestibility coefficients on the levels of qualitative feed restriction, except for acid detergent fiber, which presented a quadratic response (P<0.05). Contents of total solids (P<0.01), volatile solids (P<0.05), and total minerals (P<0.001) in the feces augmented with increasing levels of qualitative feed restriction, whereas the levels of K (P<0.05), Cu (P<0.01), N, P, Na, Ca, Mg, Fe, and Zn (P<0.001) presented a quadratic response. Daily feces excretion; and contents of total solids, volatile solids, total minerals, and levels of N, P, K, Mn, and Cu (P<0.001) and Ca, Na, Mg, and Fe (P<0.05) presented a clear increase in function of the qualitative feed restriction level. Qualitative feed restriction can be an alternative for the disposal of agribusiness waste, providing good crop-fertilizing by the use of swine feces.
Restrição alimentar qualitativa para suínos pesados: efeito sobre digestibilidade e peso dos órgãos do trato digestório e impacto ambiental das fezes
Keywords: Swine; fecal composition; energy dilution; mineral excretion; fermentable fiber; insoluble fiber; Suíno; composição fecal; diluição de energia; excreção mineral; fibra fermentável; fibra insolúvel